樹木―ツンドラ移行帯におけるパッチ状植物群集の集合メカニズム - 西澤, 啓太; 北川, 涼; 増本, 翔太; 内田, 雅己; 森, 章; Keita, Nishizawa; Ryo, Kitagawa; Shota, Masumoto; Masaki, Uchida; Akira, Mori (2017)
第8回極域科学シンポジウム/個別セッション：[OB] 極域生物圏 12月5日（火）国立極地研究所 3階多目的会議室 The Eighth Symposium on Polar Science/Ordinary sessions: [OB] Polar Biology Tue. 5 Dec./3F Multipurpose Conference Room, National Institute of Polar Research conference object